IDEOLOGICAL CONSTRUCTION IN GEN Z’S SLANG ON INSTAGRAM: A CRITICAL DISCOURSE ANALYSIS - Amalia, Nabila Dhea Putri; Budiwati, Tri Rina (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This research aims to examine textual features, investigate discursive practices, and analyze social practices that reveal the ideological constructions embedded in Gen Z’s slang on Instagram, utilizing Norman Fairclough’s three-dimensional model of Critical Discourse Analysis (CDA). Data were obtained from 31 purposively selected public Instagram posts that contained frequently used slang expressions, such as "delulu," "roasting," and "rizz." The analysis was conducted through three interrelated stages: textual analysis (examining linguistic patterns, metaphors, and emojis), discursive practice analysis (exploring production, circulation, and audience interpretation), and social practice analysis (interpreting the broader ideological context). Findings reveal that Gen Z’s slang reflects ideologies of individualism, irony, authenticity, and digital resistance, functioning not only as a linguistic trend but also as a discursive tool for negotiating power and identity in online communication. This study contributes to a deeper understanding of how language and ideology intersect within contemporary digital discourse, highlighting the socio-cultural significance of youth language in shaping online interactions.